BAGAIMANAKAH PEREKONOMIAN ANTAR KABUPATEN/KOTA DI PROVINSI LAMPUNG, KONVERGEN ATAU DIVERGEN ? - Ahmad Dhea Pratama; I Wayan Suparta; Arivina Ratih YT (Inovasi Pembangunan : Jurnal Kelitbangan, 2022)
The Convergence Hypothesis is still an interesting topic by looking at whether between regions are reaching the point of convergence or divergence in economic activity, the farther apart or the economic gap between regions is getting smaller. The analysis tool with multiple linear regression uses the Fixed Effect model approach, this study uses the per capita GRDP variable in the research year and the previous year. The secondary data is in the form of panel data with 15 districts and cities and the 2015-2019 research time series. The results of the study explain that there has been an absolute convergence process, this is marked by a negative and significant coefficient, an indication of the speed of reducing the economic gap by 4.8%, the time required in a process of reducing the gap from the initial gap is 14.17 years between 15 districts and cities in Lampung Province 2015-2019.